Pythium insidiosum: relato do primeiro caso de infecção humana no Brasil - Marques, Silvio Alencar [UNESP]; Bagagli, Eduardo [UNESP]; Bosco, Sandra M. G. [UNESP]; Camargo, Rosangela M. P. [UNESP]; Marques, Mariângela Esther Alencar [UNESP] (Sociedade Brasileira de Dermatologia, 2006)
A pitiose é causada por microorganismo aquático, fungo-símile, o Pythium insidiosum, patógeno de homens e animais. Observou-se um paciente com úlcera fagedênica no membro inferior, com exame anatomopatológico sugestivo de zigomicose, pouco sensível à terapêutica antifúngica, obtendo-se cura por meio de ampla exérese. A comprovação etiológica resultou de métodos moleculares, com amplificação e seqüenciamento de DNA de organismo isolado em ágar Sabouraud, observando-se 100% de analogia com seqüências de P. insidiosum depositadas no GenBank.

Pythiosis is caused by an aquatic fungus-like organism, Pythium insidiosum, pathogenic to men and animals. A patient with a phagedenic ulcer on the leg is reported. Histopathological examination was suggestive of zygomycosis, response to antifungal drugs was poor and cure was obtained by means of wide surgical excision. Etiologic diagnosis was confirmed by molecular amplification and DNA sequencing of colonies isolated in Sabouraud agar. After BLAST analysis, the sequence showed 100% identity with those of P. insidiosum deposited on the GenBank.
Pythium insidiosum: report of the first case of human infection in Brazil
Keywords: Brasil; Humanos; Pythium; Úlcera cutânea; Brazil; Humans; Pythium; Skin ulcer